Live birth rate and neonatal outcomes following interventional embolization of hydrosalpinx - Haiyan Guo; Tong Du; Qifeng Lyu; Ling Wu; Weiran Chai; Qianqian Zhu (Reproductive Health, 2022)
Plain English summary Our study indicates that interventional embolization of hydrosalpinx is one of the preferred clinical treatments for hydrosalpinx. More studies are warranted to investigate the short- and long-term effects of interventional embolization on the outcomes of pregnant women and neonates, which may provide more information about the management of hydrosalpinx.